Integrating South Sulawesi Local Food into Bioentrepreneurship Learning: A Project-Based Approach in Biology Education - Hilmi Hambali; Nurul Magfirah; Rahmatia Thahir (Ikatan Dosen Sains dan Teknologi Indonesia, 2025)
Higher education is increasingly expected to prepare graduates who are capable of translating scientific knowledge into real-world innovation while remaining responsive to local contexts and sustainable development needs. In biology education, this demand highlights the importance of integrating applied biological literacy with entrepreneurial competence through contextually grounded learning models. This study aims to examine the implementation of local food–based bioentrepreneurship learning in a department of biology education, Universitas Muhammadiyah Makassar, South Sulawesi, and to analyze how applied biological concepts are translated into product innovation, entrepreneurial competencies, and local wisdom–oriented learning outcomes. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, document analysis of student products and business reports, and expo performance documentation. The findings reveal that students systematically applied concepts in nutrition, food safety, natural pigments, and bioactive compounds to develop seven locally based products through iterative experimentation and project-based collaboration. The learning process fostered competencies in creativity, problem-solving, applied biology literacy, cost analysis, communication, and teamwork, while positioning local food not merely as raw material but as a regional identity and innovation resource. The study’s novelty lies in the development of an analytical framework that maps local wisdom (regional food resources and cultural identity) to biological reasoning and entrepreneurial translation within higher education. The study concludes that integrating local food into bioentrepreneurship learning strengthens contextual relevance, sustainability awareness, and applied scientific competence. This research contributes to the field of local wisdom in education by demonstrating how regional knowledge systems can function as dynamic pedagogical assets that bridge disciplinary science, entrepreneurship, and sustainable regional development.